Size Matters: Economies of Scale in European Payment Processing - Christine Beijnen; Wilko Bolt (FIW - Research Centre International Economics, 2008)
This paper investigates the existence and extent of economies of scale in the European payment processing industry. It is expected that the creation of a Single European Payments Area (SEPA) will spur consolidations and mergers among European payment processors to more fully realize payment economies of scale. We find evidence for the existence of significant economies of scale using data of eight European payment processors during the years 1990-2005. The analysis also reveals that ownership structure is an important factor to explain cost differences across European ACHs.
Keywords: E41; 330; Payment Scale Economies; SEPA; ACHs; ownership